Czas kresu czasów w literaturze apokaliptycznej - Paciorek, Piotr M. (Vox Patrum, 2014)
In this article titled “The Time of the End of Times in the Apocalyptical Literature” the author presents the study about the biblical vision of the final time which concern two domains christological and ecclesiological. This patristic study pertains to several subjects set forth in section and sub-section titles, such as: Christ as the Eternal Day of God, the Parousia as the Second Coming of Christ, the Day of Judgement, the Great Tribulation or Persecution (Mt 24: 21; Mk 13: 19; por. Dan 12: 1), “the great distress” (Rev 7: 14), the time of Pagans persisting for forty two months, the fall of Jerusalem (Mt 24: 1-3; Mk 13: 1-4; Lk 21: 5-7. 20), “abomination of desolation” (Dan 9: 27; 11: 3; 12: 11), Gog and Magog from the vision of Ezekiel (Ezek 38-39) and Apokalypse (Rev 20: 8), a great apostasy will be a prelude to the Second Coming of Christ, “a hundred and forty-four thousand who had his [Lamb’s] name and his Father’s name written on their foreheads [and] who had been ransomed from the earth” (Rev 14: 1. 3), Antichrist (1Jn 2: 18. 22; 4: 2-3; 2Jn 7) and his time three and a half years (Rev 11: 9. 11) or forty-two months (Rev 11: 2; 13: 5). The Antichrist refers to the ruling spirit of error, the enemy of the Gospel, and the opponent of Christ who will precede His Second Coming and the end of the world. He is the incarnation of wickedness, pride, and hostility toward Christ’s redemptive work. This section delves into the number 666 (Rev 13: 18; 15: 2), false prophets (2Pet 2: 1), false teachers (2Pet 2: 1). In the biblical apocalyptic literature we can find a few visions of the cosmic catastrophes and cataclysms such as “earthquakes” (Mt 24: 7; Mk 13: 8), “famines” (Mt 24: 7; Mk 13: 8). In this study, appeared the theory of Millenarianism (from Latin mille) or chiliasm (from Greek c…lioi) based on a literal interpretation of Apocalypse (Rev 20: 2-7) which interpretation teaches that the visible personal rule of Christ on earth will last for a duration of a thousand years before the end of the world. Two themes are given special study in this article. First is the distinction of the interpretation of time. Second, is the interpretation of the prophetic announcements and eschatological visions from the Bible, and the potential influence of the ancient apocalyptic stories and writings in the redaction of the Bible. As to the first theme, the application of Greek distinction of concept of time as duration (crÒnoj) from time as fulfilment and accomplishment (kairÒj) to the Hebrew conception of time is problematic. Substantial biblical concept of time is an event which pertains to time, otherwise as time having specific event, more then a time extending indefinite time. In the theological perspective, perception of time is therefore an action of God. From the very beginning to the end of Biblical History, time is the means of God’s deeds of salvation. Thence for the biblical author, the historic-redemptive (salvation) concept of the world appears before his metaphysical conception. This concept is also readily apparent in the description of the seven days from the ancient Semitic cosmogony well-known from the Book of Genesis. This topic contains an important christological and messianic aspect. The history of the world become conditioned and dependant, defined and designated by the existence of the Word of God, Creation and Incarnation by the birth of the Son of God, fulfilment of time by the second coming of the Son of Man siting at the right hand of God (Mk 16: 19; Heb 12: 2), the end of time by the judgement of God. One can speak of christological concept of time and also of christological concept of the world. The discussion of the second theme revolves around the interpretation of the Fathers of the Church on apocalyptic writings. This analysis of the meaning of the apocalyptical symbols is presented according to the interpretation of the Fathers of the Church, starting with all commentary of the Book of Revelation written from the beginning to the 12th Century. Outstanding among Greek and Latin writers from the ancient time through the Middle Ages are: Papias of Hierapolis, Justin Martyr, Hippolytus, Irenaeus of Lyon, Origen, Tertullien, Lactance, Eusebius of Caesarea, Didymus of Alexandria, Victorinus of Pettau, Gregory of Nyssa, Jerome, Augustine of Hippo, Quodvultdeus, Primasius, Caesarius of Arles, Gregory the Great, Isidore of Seville, Raban Maur, Bede the Venerable, Ambroise Autpert, Beatus of Liébana, Rupert of Deutz, Joachim of Fiore, Richard of Saint-Victor. It is well known that, between the years 200 B.C. and 150 A.D., prophetic writings appeared in certain Jewish or Christian circles. These prophetic writings were called Apocalypses. After a careful analysis, this article hypothesizes that the Bible is influenced by this ancient apocalyptic literature. The Biblical Apocalyptic Literature was dependent upon formularies and expressions used in the ancient Apocalyptic Literature. Some symbols or apocalyptic numbers were accepted from the ancient Literature, sometimes diminishing and sometimes enlarging their meaning. On the basis of formularies and symbols from Biblical Apocalyptic, the Fathers of the Church built their own historical-theological interpretation of eschatological events. In the Bible, both Old and New Testaments, there are prophetic announcements and eschatological visions. The New Testament is a repetition of those visions and those announcements made in the Old Testament. The Book of Revelation is the conclusion of those announcements and the accomplishment of those visions. An example of this use of the apocalyptical symbols in the theological and historical contexts by the Christian writers is found in the interpretation of the vision of Gog and Magog. The vision of the Gog and Magog was usually interpreted in the historical context. They were identified with Goths, Barbaric people who invaded and conquered most of the Roman Empire in the 3rd, 4th, and 5th centuries. Yet this epic figure is reinterpreted with the turn of each new century. In the new historical context, the writers give a new interpretation, but the theology of these symbols remains the same.